Legitimidade constitucional da atuação internacional dos municípios brasileiros: uma leitura à luz da teoria da Constituição Dirigente - Laisner, Regina Claudia [UNESP]; Simini, Danilo Garnica (Centro de Ensino Unificado de Brasilia, 2017)
The 1988 Constitution should be considered as an innovative document in the recognition of municipalities as federated entities responsible for meeting the ever-widening public demands in a democratic society. It occurs that, in a more immediate reading of the Charter, as a mere definition of competences, it would only be up to the Union to function as an international activity, which would restrict the increasingly common initiative of many Brazilian municipalities in this matter. This article proposes an alternative reading of the international performance of municipalities, which seeks to recognize their constitutional legitimacy, from the point of view of the Constitution, in addition to its importance as a tool for public management and addressing regional challenges. This reading is developed in the article, based on a bibliographical review on constitutional dirigism, in its relations with the most recent theoretical and practical debate of the international action of municipalities, and complemented from the bibliographical analysis of article 3 of the constitutional text, which Enunciates objectives for the State and society and give greater substance to the perspective on the screen. What can be noticed, completed the development of the work, is that this reading allows to legally recognize the international performance of municipalities, insofar as it has developed in Brazil, has shown compatibility with the fundamental objectives of the Federative Republic of Brazil listed In article 3 of the Federal Constitution of 1988. Moreover, such a vision reinforces and stimulates the role of these subnational actors as proponents and promoters of public policies and development, in their intersections between local and global.
Constitutional legitimacy of the international performance of the Brazilian municipalities: A reading in light of the theory of the Constitution Director
Keywords: Carta Magna; Directing constitution; International action of municipalities; Local development; Public policy